No Mobile Phone Phobia di Kalangan Mahasiswa Pascasarjana - Aziz, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research was conducted with the aim to find out the symptoms of no mobile phone phobia (nomophobia) among graduate students UIN Sunan Kalijaga Yogyakarta as well as knowing how the process of mentoring for students nomophobia sufferers by counselors. This research uses qualitative research methods with the phenomenology of approach. Research data obtained from observations and interviews and then data analyzed by the reduction of data, display data and tethering conclusion. The subject of this research is the 16 graduate students UIN Sunan Kalijaga Yogyakarta. The research results obtained in this study show that graduate students using a smartphone or gedget ± 12 hours in a day so the use of a smartphone with a long duration will negatively affect for the body particularly the brain. Next mentoring can be done by a Counsellor for the client that is experiencing the symptoms of nomophobia is using telephone counselling. Phone counseling provides access and control to the client so that the client can request the assistance of a Counsellor anytime and anywhere and can disconnect a telephone in accordance with his wishes